4CPS-088 Effectiveness of glecaprevir/pibrentasvir for the treatment of chronic hepatitis C. (March 2019) - Burgui, C; Juanbeltz, R; Castilla, J; Larrayoz, B; Sarobe, M; Zozaya, JM; Gracia-Ruiz de Alda, M; San Miguel, R
Abstract : Background: The availability of new pangenotypic direct-acting antiviral (DAA) combinations has simplified the treatment of chronic hepatitis C. Clinical trials have shown high rates of sustained virological response (SVR), but there is a paucity of data in a real-life context. Purpose: To assess the effectiveness of glecaprevir/pibrentasvir (GLE/PIB), a pangenotypic DAA combination, for the treatment of hepatitis C virus (HCV) infection. Material and methods: A retrospective observational study for patients treated with GLE/PIB between November 2017 and April 2018 in a reference hospital. Variables analysed: sex, age, genotype, previous HCV therapy, HIV co-infection, METAVIR score (F0-F4) and DAA treatment duration. Effectiveness was evaluated as SVR12, defined as HCV-RNA titres<15 IU/mL 12 weeks after the end of treatment (post12). Data were collected from medical records and the database of drug dispensation by hospital pharmacists. Results: One-hundred and one patients were included (59% men). Median age was 51 years (22–74). HCV genotypes: 30% G1a; 19% G1b; 1% G1 no-subtyped; 4% G2; and 28% G3 and 18% G4. Eleven patients had failed prior treatment (10 with interferon therapy and one with sofosbuvir/ledipasvir). Twenty-six per cent of patients were HIV co-infected. Fibrosis grade was 12% F4; 10% F3; 20% F2; and 58% F0–F1. Patients were treated for 8 weeks (n=88) or 12 weeks (n=13). At the end of treatment one patient had positive viral load (VL) (G3, naïve, F2, monoinfected, 8 weeks of treatment). At post12, data on VL was available in 91 patients. Eighty-nine patients have eliminated HCV infection and two rebounded (G3, naïve, F0, monoinfected, 8 weeks of treatment and G2, naïve, F0, co-infected, 8 weeks of treatment). Ten patients had not yet had their VL analysed (three were lost to follow-up and seven will be available soon). Per protocol analysis, the rate of SVR was 97% (95% CI, 94 to 100), 97% in monoinfected vs 96% in co-infected patients. The most common adverse events were fatigue and headache, although treatment was well tolerated (85% any adverse event). Conclusion: The combination GLE/PIB was effective with a high SVR12 rate, 97%. Co-infected and monoinfected patients had a similar response with an optimal safety profile. References and/or acknowledgements: EIPT-VHC project funded by the Spanish Ministry of Health and Carlos III Institute of Health. No conflict of interest.